Analysis of Crooked Cane Carrier Shafts in a Sugar Factory: Analisis Poros Pembawa Tebu Bengkok di Pabrik Gula - Puspawarna, Rangga Bayu; Fahruddin, A’rasy (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the deformation of Cane Carrier shafts under overload in sugar mills, pinpointing overload and inadequate maintenance as key culprits. Recommendations include revised load management, rigorous preventive maintenance, and systematic overload monitoring. These strategies promise to reduce shaft damage and enhance mill efficiency, presenting crucial advancements for mechanical engineering and the sugar industry. Highlight : Overload and Maintenance: Identifies overload and insufficient maintenance as principal causes of shaft damage. Preventive Strategies: Recommends enhanced load management and rigorous preventive maintenance to prevent future issues. Operational Improvement: Proposes regular overload monitoring to improve operational efficiency in sugar mills. Keywords: Cane Carrier Shaft, Overload Damage, Preventive Maintenance, Operational Efficiency, Load Management